Monolayer Doping via Phosphonic Acid Grafting on Silicon: Microscopic Insight from Infrared Spectroscopy and Density Functional Theory Calculations - Longo, Roberto C.; Cho, Kyeongjae; Schmidt, Wolf Gero; Chabal, Yves J.; Thissen, Peter (Advanced Functional Materials)

Optical response of stoichiometric and congruent lithium niobate from first-principles calculations - Riefer, Arthur; Sanna, Simone; Schindlmayr, Arno; Schmidt, Wolf Gero (Physical Review B)
The frequency-dependent dielectric function and the second-order polarizability tensor of ferroelectric LiNbO3 are calculated from first principles. The calculations are based on the electronic structure obtained from density-functional theory. The subsequent application of the GW approximation to account for quasiparticle effects and the solution of the Bethe-Salpeter equation for the stoichiometric material yield a dielectric function that slightly overestimates the absorption onset and the oscillator strength in comparison with experimental measurements. Calculations at the level of the independent-particle approximation indicate that these deficiencies are, at least, partially related to the neglect of intrinsic defects typical for the congruent material. The second-order polarizability calculated within the independent-particle approximation predicts strong nonlinear coefficients for photon energies above 1.5 eV. The comparison with measured data suggests that the inclusion of self-energy effects in the nonlinear optical response leads to a better agreement with experiments. The intrinsic defects of congruent samples reduce the optical nonlinearities, in particular, for the 21 and 31 tensor components, further improving the agreement between experiments and theory.

Structural variety of 5-fluoroarene-2-aminopyrimidine in comparison to 2-aminopyrimidine silver(i) coordination polymers: progress report and overview - Eberhard, Jens; Stoll, Ion; Brockhinke, Regina; Neumann, Beate; Stammler, Hans-Georg; Riefer, Arthur; Rauls, Eva; Schmidt, Wolf Gero; Mattay, Jochen (CrystEngComm)

Bis-μ-oxo and μ-η2:η2-peroxo dicopper complexes studied within (time-dependent) density-functional and many-body perturbation theory - Rohrmüller, M.; Herres-Pawlis, S.; Witte, M.; Schmidt, Wolf Gero (Journal of Computational Chemistry)

Atomic Structure of Interface States in Silicon Heterojunction Solar Cells - George, B. M.; Behrends, J.; Schnegg, A.; Schulze, T. F.; Fehr, M.; Korte, L.; Rech, B.; Lips, K.; Rohrmüller, M.; Rauls, E.; Schmidt, Wolf Gero; Gerstmann, U. (Physical Review Letters)

LiNb1-xTaxO3Electronic Structure and Optical Response fromFirst-PrinciplesCalculations - Riefer, A.; Sanna, S.; Schmidt, Wolf Gero (Ferroelectrics)

Analytic evaluation of the electronic self-energy in the GW approximation for two electrons on a sphere - Schindlmayr, Arno (Physical Review B)
The GW approximation for the electronic self-energy is an important tool for the quantitative prediction of excited states in solids, but its mathematical exploration is hampered by the fact that it must, in general, be evaluated numerically even for very simple systems. In this paper I describe a nontrivial model consisting of two electrons on the surface of a sphere, interacting with the normal long-range Coulomb potential, and show that the GW self-energy, in the absence of self-consistency, can in fact be derived completely analytically in this case. The resulting expression is subsequently used to analyze the convergence of the energy gap between the highest occupied and the lowest unoccupied quasiparticle orbital with respect to the total number of states included in the spectral summations. The asymptotic formula for the truncation error obtained in this way, whose dominant contribution is proportional to the cutoff energy to the power −3/2, may be adapted to extrapolate energy gaps in other systems.

Zur Handlungsvalidität von Tests zum professionellen Wissen von Lehrkräften - Vogelsang, Christoph; Reinhold, Peter (Zeitschrift für Didaktik der Naturwissenschaften)

Experimental Observation of the Spectral Gap in Microwave n-Disk Systems - Barkhofen, Sonja; Weich, Tobias; Potzuweit, A.; Stöckmann, H.-J.; Kuhl, U.; Zworski, M. (Physical Review Letters)
Keywords: General Physics and Astronomy

Qualität inklusiven Unterrichts in der Grundschule. Symposium auf der Tagung „Gemeinsam anders lehren und lernen – Wege in die inklusive Bildung“. Gemeinsame Jahrestagung der DGfE Kommission Grundschulforschung und Didaktik der Primarstufe und der DGfE Sektion Sonderpädagogik - Hellmich, Frank; Blumberg, Eva